2007
DOI: 10.1152/japplphysiol.00538.2006
|View full text |Cite
|
Sign up to set email alerts
|

Bowman-Birk inhibitor concentrate prevents atrophy, weakness, and oxidative stress in soleus muscle of hindlimb-unloaded mice

Abstract: inhibitor concentrate prevents atrophy, weakness, and oxidative stress in soleus muscle of hindlimb-unloaded mice.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
65
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 67 publications
(67 citation statements)
references
References 36 publications
2
65
0
Order By: Relevance
“…6) suggests a source nearby (e.g., Nox2, subsarcolemmal mitochondria). Previously, Abrogast et al (4) reported that oxidative stress was elevated in unloaded skeletal muscle after 1-3 days. Bowman-Birk inhibitor complex (BBIC), which exhibits antiproteasome and antioxidant properties, significantly reduced unloading-induced fiber atrophy and reduction of force-generating capacity (4).…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…6) suggests a source nearby (e.g., Nox2, subsarcolemmal mitochondria). Previously, Abrogast et al (4) reported that oxidative stress was elevated in unloaded skeletal muscle after 1-3 days. Bowman-Birk inhibitor complex (BBIC), which exhibits antiproteasome and antioxidant properties, significantly reduced unloading-induced fiber atrophy and reduction of force-generating capacity (4).…”
Section: Discussionmentioning
confidence: 98%
“…Indeed, while some antioxidant strategies have been successful in reducing skeletal muscle atrophy with mechanical unloading (4,25,30), other interventions have not (6,20). For example, administration of BBIC significantly attenuated muscle atrophy in limb muscles (4), while Trolox was less successful (6).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…vitamin E or soya protein extract) has been published (14,101,187,188) . However, contradictory results have been obtained regarding the impact of vitamin E on muscle atrophy.…”
Section: Nutritional Interventions To Reduce the Anabolism Threshold mentioning
confidence: 99%
“…Skeletal muscular atrophy can be reproduced experimentally in rodents by hind-limb unloading. Dietary supplementation containing 1% BBIC has been reported to inhibit unloading-induced weakness in mice [89], promoting redox homeostasis in muscle fibers and blunting atrophy-induced weakness [90]. Morris et al [89] suggested that inhibiting muscle degrading proteases may provide a new pharmacological strategy in treating skeletal m u s c u l a r a t r o p h y ; h o wever, such proteases remain uncharacterized.…”
Section: Beneficial Properties Of Bowman-birk Inhibitors In Non-relatmentioning
confidence: 99%